Incidence and histopathological examination of oral leukoplakia - Botond Bukovszky; László Simonffy; Szabolcs Gyulai-Gaál; Noémi Jákob; Csaba Dobó Nagy (Fogorvosi Szemle)
Introduction: Leukoplakia is one of the most common lesions of potentially malignant lesions of the oral cavity. It is important to clarify the histopathological diagnosis underlying cases clinically diagnosed as leukoplakia, which is crucial in determining the prognosis and the required therapy. Material and Methods: 75 patients diagnosed with oral leukoplakia were histologically sampled between April 2021 and April 2024 at the Department of Oral Diagnostics, Department of Dento-alveolar Surgery, Semmelweis University. Histopathological analysis of the histopathological samples was performed on the basis of hematoxylin-eosin staining and in selected cases immunohistochemical analysis was performed at the Department of Pathology and Experimental Cancer Research. Results and discussion: The 75 patients were classified according to the location of leukoplakia in decreasing order of frequency: gingiva/ edentulous jaw ridge (n = 26), buccal (n = 16), floor of the mouth (n = 12), tongue (n = 11), palate (n = 6), lip (n = 2). Multifocal appearance was also seen (n = 2). Histological sampling was usually a partial and not total excision of the lesion. Histopathological findings were hyperkeratosis (without dysplasia) in 51 cases, 19 cases with mild dysplasia, 5 cases with moderate dysplasia. There were no cases with severe dysplasia. In 61 cases were homogeneous and in 14 cases non-homogeneous leukoplakia. Dysplasia was significantly more frequent in clinically non-homogeneous leukoplakia (p = 0.0088). 32 of the 75 patients were smokers and 43 were non-smokers. Our results showed that smoking had no significant effect on the presence and severity of dysplasia. Patients were followed up continuously (6 months follow-up). Average follow-up time: 17.4 months (range: 1–38 months). Conclusion: Patients diagnosed with oral leukoplakia require histopathological sampling for histopathological examination and long-term follow-up is recommended to prevent late malignant transformation.